Pnarmacokinetics and dosage regimen of amikacin in febrile cow calves - SAINI, S P S; SRIVASTAVA, A K (The Indian Journal of Animal Sciences, 2013)
Disposition kinetics and dosage regimen of amikacin were investigated in experimentally induced febrile male cow calves. Fever was induced with E. coli endotoxin (1ug.kg, i/v) and after induction of ever, amikacin was administered (10 mg/kg/i/v). At 1 min, the peak plasma level of amikacin was 133.6-+1.96 ug/ml and the minimum therapeutic concentrationwas maintained up to 12 hr. The distribution half-lives in perpheral compartments 1 and 2 were 0.06-+ hr and 0.068-+ 0.03 hr, respectively. The elimination half-life and volume of distribution were 4.10 -+0.13 hr and 0.35-+0.04 L/kg respectively. The values of total body clearance *(CIB) and T/P ratio were 0.05-+0.01 L/kg hr and 6.21-+0.78 respectively. To maintain the minimum therapeutic plasma concentration, the appropriate dosage regimen of amikacin in febrile cow calves would be 6 mg/kg followed by 5 mg/kg at 12 hr intervals.